2015
DOI: 10.12659/msm.893567
|View full text |Cite
|
Sign up to set email alerts
|

Association between Serum Fructosamine and Kidney Function in Nondiabetic Individuals without Chronic Kidney Disease

Abstract: BackgroundSerum fructosamine (SF) has been considered to be an indicator that estimates glycemic control in patients with diabetes mellitus (DM). There is increasing evidence that SF concentration and oxidative stress are significantly elevated in patients with chronic kidney disease (CKD). However, the data about SF and its association with kidney function are lacking in nondiabetic individuals without CKD. We included 1891 nondiabetic individuals who had not been diagnosed with CKD to determine the associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, these tools are uncommon and unavailable in the clinical laboratory. Recent studies have shown that several laboratory markers are associated with systemic inflammation and oxidative stress, such as urea nitrogen (UN), creatinine (Cr), fructosamine (SF) and bilirubin 11 12 . Unfortunately, their single use is often limited by poor sensitivity and specificity.…”
mentioning
confidence: 99%
“…However, these tools are uncommon and unavailable in the clinical laboratory. Recent studies have shown that several laboratory markers are associated with systemic inflammation and oxidative stress, such as urea nitrogen (UN), creatinine (Cr), fructosamine (SF) and bilirubin 11 12 . Unfortunately, their single use is often limited by poor sensitivity and specificity.…”
mentioning
confidence: 99%
“…Peng et al . 5 reported a positive correlation between serum fructosamine and estimated glomerular filtration rate in non-diabetic individuals. Previous studies have demonstrated that higher serum fructosamine levels were associated with coronary artery atherosclerosis, dementia and renal failure 6 9 .…”
Section: Introductionmentioning
confidence: 97%